2021
DOI: 10.1186/s13041-021-00826-2
|View full text |Cite
|
Sign up to set email alerts
|

Meningitic Escherichia coli α-hemolysin aggravates blood–brain barrier disruption via targeting TGFβ1-triggered hedgehog signaling

Abstract: Bacterial meningitis is a life-threatening infectious disease with severe neurological sequelae and a high mortality rate, in which Escherichia coli is one of the primary Gram-negative etiological bacteria. Meningitic E. coli infection is often accompanied by an elevated blood–brain barrier (BBB) permeability. BBB is the structural and functional barrier composed of brain microvascular endothelial cells (BMECs), astrocytes, and pericytes, and we have previously shown that astrocytes-derived TGFβ1 physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
(58 reference statements)
0
12
0
Order By: Relevance
“…The α-hemolysin in meningitic E. coli K1 strain has been demonstrated to reduce ZO-1 expression of hBMEC by inhibiting the TGFβ1-TGFBRII-Smad2/3-Gli1/2 axis . OmpA-mediated meningitic E.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The α-hemolysin in meningitic E. coli K1 strain has been demonstrated to reduce ZO-1 expression of hBMEC by inhibiting the TGFβ1-TGFBRII-Smad2/3-Gli1/2 axis . OmpA-mediated meningitic E.…”
Section: Discussionmentioning
confidence: 99%
“… 24 The α-hemolysin in meningitic E. coli K1 strain has been demonstrated to reduce ZO-1 expression of hBMEC by inhibiting the TGFβ1-TGFBRII-Smad2/3-Gli1/2 axis. 25 OmpA-mediated meningitic E. coli adhesion of hBMEC activated PKCα signaling, resulting in β-catenin dissociation from Cadherins, eventually leading to BBB breakdown. 26 In addition, several host molecules have been reported to mediate the enhancement of BBB permeability during E. coli meningitis, such as platelet-derived growth factor B (PDGFB), IL-17A, Snail-1, IL-1β, IL-6, and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…The hBMECs were subsequently used as in vitro model. We additionally tested the effects of IL-17A on TEER value, an important indicator of the monolayer permeability (Fu et al, 2021), by application of ECIS system. The results showed that IL-17A could dose-dependently down-regulate the TEER value of hBMECs monolayer (Figure 2C).…”
Section: Interleukin-17a Promoted the Disruption Of Blood-brain Barri...mentioning
confidence: 99%
“…Astrocytes-derived TGFβ1, and the exogenous recombined TGFβ1 (rTGFβ1) activate transcription factors of HH signaling, Gli1 and Gli2. This noncanonical HH signaling protects mice from death upon meningitic E. coli infection by maintaining BBB integrity [ 21 ]. Consideration of TGFβ1 to modulate the immunity, we presumed that TGFβ1 might also repress the BBB immune reaction while maintaining the BBB integrity.…”
Section: Introductionmentioning
confidence: 99%